2011
DOI: 10.1002/jctb.2690
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic degradation of oxygenates in Fischer–Tropsch aqueous phase effluents to fuel gas via hydrodeoxygenation over Ru/AC catalyst

Abstract: BACKGROUND: Aqueous phase Fischer-Tropsch (FT) effluents co-produced with hydrocarbons in the FT process contain various water-soluble oxygenates, e.g. carboxylic acids, alcohols. Purification of the FT aqueous phase is important from the viewpoint of effective resource utilization and environmental stewardship. In this work, an aqueous-phase hydrodeoxygenation process was investigated for the degradation of FT aqueous phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…The aqueous FT effluents, labeled Aqueous‐I, II and III, are obtained from Synfuels China Co. Ltd. which uses a co‐precipitated iron‐based slurry phase FT process. The composition of oxygenates (% (w/w)) is given in Table 1 1…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aqueous FT effluents, labeled Aqueous‐I, II and III, are obtained from Synfuels China Co. Ltd. which uses a co‐precipitated iron‐based slurry phase FT process. The composition of oxygenates (% (w/w)) is given in Table 1 1…”
Section: Methodsmentioning
confidence: 99%
“…They show the aggregation or migration of Ru particles on the surface of the catalyst, although the X‐ray diffraction (XRD) (Fig. 2) and N 2 physisorption results reveal no formation of crystalline Ru and no significant drop in surface area (dropping from 915 to 858 m 2 g −1 ) for the catalyst used 1. This indicates that the bonding of Ru particles with the oxygen‐anchoring group of the carbon surface species becomes weaker during a long‐term test in aqueous media.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[35][36][37] Relevant to the present work, Chen et al reported the degradation of oxygenates to hydrocarbons under a H 2 pressure of 98 bar using a Ru catalyst. 38,39 This reaction involves acid-catalyzed dehydration of alcohols and subsequent hydrogenation to paraffins. 40 The reaction mixture in the work of Chen et al was slightly acidic due to the presence of organic acids.…”
Section: Catalytic Activity Measurementsmentioning
confidence: 99%